Frequency of Complications and Mortality Due to Intertrochanteric Fracture of the Hip Joint in Individuals Over 60 Years of Age Receiving Vitamin D - Homa Naderifar; Saharnaz Mohammadi; Abbas Moradi; Morteza Majidi (پزشکی بالینی ابن سینا, 2022)
Background and Objective: Vitamin D deficiency in humans is a major health problem worldwide. This study aimed to investigate the effect of vitamin D supplementation in reducing mortality and complications after intertrochanteric fracture of the hip joint. Materials and Methods: In this clinical trial, 100 patients over 60 years of age with hip fractures and serum levels of vitamin D less than 20 ng/ml referring to Besat Hospital in Hamadan, Iran, were selected and randomly assigned to one of the intervention or control groups. The intervention group was given vitamin D in a vial of 600,000 units IM. Data were analyzed using SPSS software (version 23). Results: The mean age of the patients in the intervention and control groups were 78.04±8.50 and 79.40±7.30 years, respectively (P=0.430). Regarding gender, 54% of the patients in the intervention group and 60% in the control group were men. Mean serum levels of vitamin D were 15.48±4.03 and 14.23±3.28 ng/ml, respectively. The frequencies of mortality within one year after surgery were 8% and 18% (P=0.137), and the frequencies of complications were 4% and 14% (P=0.160). Conclusion: The injection of vitamin D supplement in the form of a single dose of 600,000 muscle units in patients over 60 years of age with vitamin D deficiency and intertrochanteric fracture of the hip joint reduced one-year mortality and complications. However, this reduction was not significant compared to the control group.